1982
DOI: 10.1111/j.1526-4610.1982.hed2206268.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Study of Propranolol in the Treatment of Migraine

Abstract: SYNOPSIS Out of 245 patients admitted to a two‐month single‐blind phase in a study with propranolol vs. placebo, 148 (72%) were propranolol responders. These responders were randomly assigned to propranolol or placebo for the following double‐blind phase. After four weeks, they opted to either (1) remain on the assigned drug for 6 to 12 months or (2) to switch to the other drug for 6 to 12 months. In either case, they then switched drugs for a final one or two months of the study. No tolerance was found in 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 4 publications
2
38
0
1
Order By: Relevance
“…Propranolol and flunarizine have proven to be useful tools in migraine prophylaxis 3,7,1213 . This trial aims the comparison of the efficacy of propranolol to flunarizine and to propranolol plus flunarizine in migraine prophylaxis.…”
mentioning
confidence: 99%
“…Propranolol and flunarizine have proven to be useful tools in migraine prophylaxis 3,7,1213 . This trial aims the comparison of the efficacy of propranolol to flunarizine and to propranolol plus flunarizine in migraine prophylaxis.…”
mentioning
confidence: 99%
“…Long-term trials also confirmed the efficacy of propranolol [Diamond et al, 1982]. Despite positive reports from various clinical trials on the use of other b-blockers in migraine prophylaxis, only propranolol and timolol have received approval from the FDA for the indication of migraine prevention.…”
Section: B-blockersmentioning
confidence: 83%
“…Propranolol hydrochloride is used routinely in adults at doses of 240-320mg/day for indications such as migraine prophylaxis 15,16 and essential tremor 17-19 and has been used safely in burn patients to decrease the metabolic consequences of burn injury. 20-22 Based on this safety profile and lack of established dose regimen for burn pain, a dose of 120mg BID of propranolol (240mg/day) was selected for patients receiving active study drug.…”
Section: Methodsmentioning
confidence: 99%